UDP Protocol for multi-task assignment in "void loop" robot soccer - Irma Damayanti; Simon Siregar; Muhammad Ikhsan Sani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The communication system is a very important part of the robot soccer. It is because the robots must be able to move together, alternate and individual. The communication system that would be discussed is about the process of sending data from one robot to another robot using coach computer. It started with the reception of data from coach computer to both robots that had been installed Wi-Fi Communication module that had been connected to the router. Then, the data is processed using Arduino Mega2560. After that, the robot would detect the existence of the ball. The protocol used for the communication system is a UDP protocol (User Datagram Protocol) because UDP has several characteristics that support the occurrence of communication robots such as connection-less and unreliable. Both of characteristics have a faster connection, they do not require handshaking and UDP protocol provides a mechanism for sending a message to a specific process. The result shows that the communication system between coach computer and both robots is successful. This is indicated by the start button and stop button is 100% with repeating data transfer system on UDP protocol.